(untitled) (Research, Society and Development, 2020)
The recent outbreak of COVID-19 in China was considered a serious public health problem by the World Health Organization (WHO), an examination that there is no vaccine or medicine capable of causing or treating diseases, but it is Chinese medicine with its herbal products, it is recommended to use some herbs to avoid COVID-19, including the oral administration of some of these herbal medicines. The occurrence of COVID-19 has spread worldwide, and cases have been reported in several countries, so the World Health Organization (WHO) declared a pandemic, among the affected countries are China, Italy, Spain, United States and Brazil. This is an integrative review on aspects of the COVID-19 pandemic, appearance, symptoms, and data on herbal medicines related to the prevention of this disease. This review was based on the publications in the PUBMED database with articles from the year 2020. Traditional Chinese medicine has brought hope for prevention and treatment in some research, as it already plays an important role in the treatment of other pathologies. In China, during the outbreak of COVID-19, hospitals specialized in traditional medicine using plants were established. medicinal, in search of a collective and effective treatment, which treated more than 60,000 patients.